Evaluating China's mental health policy on local-level promotion and implementation: a case study of Liuyang Municipality - Wei Zhou; Yu Yu; Xinyi Zhao; Shuiyuan Xiao; Lizhang Chen (BMC, 2019)
Abstract Background Since 2000, a series of national policies have been released to tackle mental health problems in China; however, their promotion and implementation at local level are under-evaluated. This study will evaluate the case of Liuyang Municipality, to present a deeper understanding of China's problems and lessons on implementation of mental health policy in developing countries. Methods A rapid appraisal was conducted on Liuyang's mental health policy and plan, under two evaluation frameworks: (1) the WHO checklists for mental health policy and plan, (2) activities and time frames stated in Liuyang's mental health policy and plan. Documentation review, semi-structured interviews with nine key informants, and surveys on 32 front-line implementers were performed. Descriptive statistics and framework analysis were employed respectively to analyze quantitative and qualitative data. Results As a local-level promotion of national mental health policies, Liuyang's mental health policy and plan had evidence base and received highest-level approval within local health system, but without stakeholders' consultation. The vision, principles and objectives were consistent with national policies. Twelve WHO-suggested areas for actions were unequally covered. Policy content had operational defects of lacking necessary details on evaluation, funding and activity. For implementation, health departments generally outperformed non-health ones. Discrepancies between planning and practices, and uneven regional implementation compromised implementation quality. Insufficient and poorly trained human resources, unguaranteed funding and low client acceptability were identified as implementation barriers. Conclusions The case of Liuyang is an active attempt to promote and implement national mental health policies at local level. As a reflection of mental health policy in China and developing countries, its highlights and problems demonstrate that evidence base, high-level approval, multi-sector involvement, operational content, and clear focuses promote policy implementation.